2004
DOI: 10.1253/circj.68.671
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Level of Monocyte Chemoattractant Protein-1 in Human Atherosclerosis-Assessment in Chronic Hemodialysis Patients-

Abstract: he rates of cardiovascular or cerebrovascular mortality related to accelerated atherosclerosis are high in patients undergoing chronic hemodialysis (HD) treatment. 1,2 The overall cardiovascular mortality rate in patients undergoing chronic HD treatment is estimated to be approximately 30%, of which 10% are deaths because of myocardial infarction. 3 Recently, it has been shown that monocyte chemoattractant protein-1 (MCP-1) is a potent monocyte chemoattractant and largely responsible for the recruitment of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 39 publications
1
47
0
1
Order By: Relevance
“…MCP-1, the prototypical CC chemokine, has been associated with chronic vascular disorders including atherosclerosis, unstable angina, and congestive heart failure, as well as with certain inflammatory states. 17 In our study, cardiac syndrome X patients were found to have significantly higher MCP-1 levels than were observed in the normal controls and MCP-1 might play a crucial role in the pathogenesis of cardiac syndrome X.…”
Section: Discussionsupporting
confidence: 45%
“…MCP-1, the prototypical CC chemokine, has been associated with chronic vascular disorders including atherosclerosis, unstable angina, and congestive heart failure, as well as with certain inflammatory states. 17 In our study, cardiac syndrome X patients were found to have significantly higher MCP-1 levels than were observed in the normal controls and MCP-1 might play a crucial role in the pathogenesis of cardiac syndrome X.…”
Section: Discussionsupporting
confidence: 45%
“…MCP-1, acting through its receptor CCR2, appears to play an early and important role in the recruitment of monocytes to atherosclerotic lesions, 15 and it has been suggested that the serum concentration of MCP-1 is an independent risk factor for progression of atherosclerosis. 16 CB (100 g/ml, 24 h) significantly increased the production of MCP-1 in HUVECs (Fig 7A, 55.1±14.2 pg/ml in control vs 366.0±26.0 pg/ml in CB, n=5, p<0.01). Vascular cell adhesion molecule (VCAM)-1 participate in the recruitment of leukocytes by inducing their firm adhesion to the activated endothelium.…”
Section: Effects Of Cb On Huvecsmentioning
confidence: 88%
“…Prostaglandin E1 inhibits platelet and neutrophil activity and may inhibit endothelial activation by impaired adhesion of blood cells and other mechanisms. 27 Recently, Kusano et al 28 found that the MCP-1 serum level and intima -media thickness correlated with each other in patients on chronic hemodialysis. They also found that MCP-1 was expressed in endothelial and smooth muscle cells in these patients.…”
Section: Discussionmentioning
confidence: 99%